First reported case of a spontaneous and healthy pregnancy in a woman with persistent CAR T-cells 5 years after treatment for diffuse large B-cell lymphoma - Andrew A White; Lori Broderick; Ethan Abraham Canty; Daniel Flaherty; Marin Xavier; Sunita D Nasta; Lina Dajani (Journal for ImmunoTherapy of Cancer)
Chimeric antigen receptor T-cell (CAR T-cell) therapy has significantly advanced cancer treatments and remission rates; however, questions exist regarding the impacts on both fertility and immune effects on infants born to mothers who have undergone CAR T-cell therapy. There are no known reported cases of persistence of CAR T-cells after cancer therapy in pregnancy. Here, we present a case of a woman with relapsed refractory diffuse large B-cell lymphoma who undertook an experimental CAR T-cell therapy, had persistence of CAR T-cells 5 years after achieving remission, spontaneously became pregnant and delivered a healthy male infant. Our case provides an example of a healthy pregnancy despite the persistence of CAR T-cells and the resultant healthy newborn without evidence of immunologic or other health effects from the CAR T-cells.